Integrating killer cell immunoglobulin-like receptor high-resolution genotyping for predicting transplant outcomes in allogeneic hematopoietic stem cell transplantation - Antonia Schäfer; Stéphane Buhler; Ticiana D.J. Farias; Katherine M. Kichula; Helen Baldomero; Zuleika Calderin Sollet; Sylvie Ferrari-Lacraz; Baptiste Micheli; Stavroula Masouridi-Levrat; Vanessa Mesquita; Oliver Kürsteiner; Gayathri Nair; et al. (Haematologica)
The success of hematopoietic stem cell transplantation (HSCT) partly relies on the beneficial graft-versus-leukemia effect, mediated by alloreactive NK cells through their killer cell immunoglobulin-like receptors (KIR). Conflicting results have been reported regarding the impact of the KIR immunogenetic system on HSCT outcomes with a scarcity of data interrogating the effect of KIR allelic polymorphism. With the aim to fill this gap, donor KIR genes derived from a national cohort of 1247 HLA-matched transplanted donor/recipient pairs were determined at a high-resolution and tested in Cox proportional hazards models. Donor/recipient (D/R) pairs bearing a KIR2DS4*00101 – HLA-C1/C2/A11 interaction showed a significant detrimental impact on progression-free survival (PFS), overall survival (OS), transplant-related mortality (TRM) and chronic graft-versus-host disease (cGvHD) in multivariable analysis. Strong KIR2DL2/L3 – HLAC1 and especially KIR2DL3*00501 and *015 interactions showed a significant increase in the incidence of cGvHD compared to missing ligand D/R pairs. Highly inhibiting KIR3DL1 – HLA-B and HLA-A (Bw4) interactions were associated with a reduced relapse incidence as compared to weak and non-inhibiting interactions. Our study indicates that high-resolution KIR genotyping informs post-transplant outcomes with a seemingly higher protection of educated NK cells.